2016
DOI: 10.1111/pcn.12402
|View full text |Cite
|
Sign up to set email alerts
|

Internet addiction: Prevalence and relation with mental states in adolescents

Abstract: Aim: Internet addiction disrupts the daily lives of adolescents. We investigated the prevalence of Internet addiction in junior high school students, elucidated the relation between Internet addiction and mental states, and determined the factors associated with Internet addiction in adolescents.Methods: Junior high school students (aged 12-15 years) were assessed using Young's Internet Addiction Test (IAT), the Japanese version of the General Health Questionnaire (GHQ), and a questionnaire on access to electr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
127
3
5

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 154 publications
(148 citation statements)
references
References 20 publications
13
127
3
5
Order By: Relevance
“…Also, results showed that Internet addiction score increased in the same direction with all general health aspects. Several studies confirm the current results (12)(13)(14). Gholamian et al's study showed that anxiety, depression, and stress were significantly higher in Internet addicted users (14).…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…Also, results showed that Internet addiction score increased in the same direction with all general health aspects. Several studies confirm the current results (12)(13)(14). Gholamian et al's study showed that anxiety, depression, and stress were significantly higher in Internet addicted users (14).…”
Section: Discussionsupporting
confidence: 72%
“…The desired level of general health status was observed in users, who had mild level of addiction to the Internet (11). In addition, in the study of Kawabe et al in 2016 on 12-to 15-year-old high school students in Japan, Internet addicted students had high general health scores (12). Another study on Internet addiction and its psychological effects performed on nursing students in Gaza and Palestine in 2014 showed a positive and significant relationship between Internet addiction and psychological effects (13).…”
Section: Introductionmentioning
confidence: 99%
“…Fifth, the IAT was developed about two decades ago under conditions where Internet access was limited, and therefore the cut‐off values of IAT 40 might be inappropriate to define ‘problematic’ Internet use now. As the IAT includes questions regarding dysfunctionality associated with Internet use (such as ‘How often do your job performance or productivity suffer because of the internet?’), we considered IAT to still be usable today, in addition to the fact that many studies to date have used the scale . However, we believe that the invention of a new scale to better fit modern Internet use is required in the near future.…”
Section: Discussionmentioning
confidence: 99%
“…You may surf the Web a bit too long at times, but you have control over your usage.’). In this study, we defined subjects with an IAT ≥ 40 as the PIU group and those with an IAT ≤ 39 as the non‐PIU group, as similarly defined in some previous studies …”
Section: Methodsmentioning
confidence: 99%
“…Although Kawabe et al . reported that PIU was related to the mental health of junior high‐school students in the suburbs of Ehime, studies on its relationship with lifestyle habits, such as sleep and study time, that might lead to the early detection of junior high‐school students with PIU have been scarce. Moreover, PIU may be related to orthostatic dysregulation (OD), ‘a functional physical disorder with an impairment of circulatory adjustment against gravitational stress because of dysregulation of the autonomic nervous system.’ The main factors of OD have been thought to be psychological stress and changes in adolescents’ hormone balance .…”
mentioning
confidence: 99%